2022
DOI: 10.3847/1538-4357/ac313f
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Broad Lyα Line Emission from the Molecular Intragroup Medium in Stephan’s Quintet: Evidence for a Turbulent Cascade in a Highly Clumpy Multiphase Medium?

Abstract: We present Hubble Space Telescope Cosmic Origin Spectrograph (COS) UV line spectroscopy and integral-field unit (IFU) observations of the intragroup medium in Stephan’s Quintet (SQ). SQ hosts a 30 kpc long shocked ridge triggered by a galaxy collision at a relative velocity of 1000 km s−1, where large amounts of molecular gas coexist with a hot, X-ray-emitting, plasma. COS spectroscopy at five positions sampling the diverse environments of the SQ intragroup medium reveals very broad (≈2000 km s−1) Lyα line emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 66 publications
(79 reference statements)
1
20
0
Order By: Relevance
“…They may be evidence for shocks associated with cloud collisions. Similar examples of very faint star formation embedded in shocked intergalactic emission-line gas exhibiting multiple line profiles is observed in Stephan's Quintet (see, for example, Xu et al 2003;Konstantopoulos et al 2014;Guillard et al 2022).…”
Section: The Extragalactic H II (X-h Ii) Region and Its Ionized Gassupporting
confidence: 52%
See 2 more Smart Citations
“…They may be evidence for shocks associated with cloud collisions. Similar examples of very faint star formation embedded in shocked intergalactic emission-line gas exhibiting multiple line profiles is observed in Stephan's Quintet (see, for example, Xu et al 2003;Konstantopoulos et al 2014;Guillard et al 2022).…”
Section: The Extragalactic H II (X-h Ii) Region and Its Ionized Gassupporting
confidence: 52%
“…The other samples are the same as those described in Figure 9. (Guillard et al 2022) combined with previous observations of molecular hydrogen and X-rays (Appleton et al 2017;O'Sullivan et al 2009) show strong evidence that the dissipation of kinetic energy involves all gas phases. These are likely connected through a turbulent cascade involving atomic and molecular magnetohydrodynamic shocks (Lesaffre et al 2020;Durrive et al 2021), and turbulent mixing layers (Slavin et al 1993).…”
Section: Origin Of the Star Formation Suppression In The Bridgementioning
confidence: 55%
See 1 more Smart Citation
“…Stephan's Quintet (SQ, co-moving radial distance = 85 ± 6 Mpc, taken from the NASA/ IPAC Extragalactic Database (NED) 1 ) is unique among compact groups of galaxies [2][3][4][5][6][7][8][9][10][11][12] . Observations have previously shown that interactions between multiple members, including a high-speed intruder galaxy currently colliding into the intragroup medium, have probably generated tidal debris in the form of multiple gaseous and stellar filaments 6,8,13 , the formation of tidal dwarfs 7,14,15 and intragroup-medium starbursts 16 , as well as widespread intergalactic shocked gas 5,10,11,17 . The details and timing of the interactions and collisions remain poorly understood because of their multiple nature 18,19 .…”
mentioning
confidence: 99%
“…It is believed that in SQ, galaxy-galaxy and galaxy-IGM interactions have led to the complete removal of HI gas from its member galaxies 6,20 , a large-scale shocked lament ∼ 40 kpc in length 8 , an IGM starburst 9 , and long tidal tails (> 100 kpc) with tidal dwarf candidates 10 . It is a unique laboratory for studies of various processes associated with high-speed galaxy-galaxy/IGM collisions, such as the heating and cooling of warm H 2 gas powered by large scale shocks 11,12 , SFR quenching by turbulence in post-shock molecular gas 13 , and the possible transition of galaxies through the Green Valley (the evolutionary stage between star-forming galaxies and quiescent galaxies) during the evolution of compact groups 14,15 .A comprehensive understanding of the properties of SQ depends crucially on how accurately we know its interaction history, which is very complex due to the relatively large number (> 5) of participants.Theoretical simulations have yielded inconclusive and controversial results. The ducial model in Ref.…”
mentioning
confidence: 99%